Action - "Taylor, Kim" (Belitha Press Ltd: London, 1991)
One of a series which aims to help children look more closely at the world in which they live, this book on action juxtaposes elements from the natural and mechanical world. Using photographic sequences and illustrations the text examines the reasons behind the way things function.